Environment, health and migration: Towards a more integrated analysis - Jennifer Holdaway (United Nations Research Institute for Social Development (UNRISD), 2014)
This commentary is part of a series of papers that considers the challenges that rural-urban migration in China presents for health policy. Several of the contributions begin with a listing of the factors that put migrants health at risk and many of these relate to "the environment" They include exposure to a range of physical, chemical or biological hazards in the home and workplace as well as psychological stresses related to the social environment. The first part of this paper discusses the ways in which environmental factors can affect health, reviews the main trends in research on this topic in the China context and discusses some of its limitations and challenges. In particular, it points to the fact that to date most research has focused on assessing existing health outcomes and risks, and has paid little attention to their drivers. This severely limits the usefulness of these studies in anticipating future shifts in the burden of disease and informing policies to address them. The second part of the paper expands the frame of the analysis and argues more broadly for grounding research on environment, migration and health in analysis of the spatial distribution of economic activities and population which shape locally specific constellations of environment and health problems. This broader perspective is especially necessary at a time when industrial restructuring, agricultural intensification and urbanization are redefining Chinas physical and social landscapes.
Keywords: 330